(3cJGH GdJOGQc dCfhGY NWGA GdJOGHjQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEf GdTjN CHG GdMSf CMeO Hf eMeO GdSgdi ai YQa HYdhG GdgeI CeQfi ajeG GeQ ef GdChGeQ GdMcejI Cf CYed cJGHkG ai OaY GdeVGQ GdcdjI ddCHOGf GdCfSGfjI s
(3BNQgG (B:s
(3hjSJYjf HGdfhe aEfg GdCUd aEf NQL ZjQ efgVe hdjcf gPG cGa ai ZQVfG hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B380s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs